Sustained delivery of PARP inhibitor Talazoparib for the treatment of BRCA-deficient ovarian cancer - Yang, Shicheng; Green, Allen; Brown, Needa; Robinson, Alexis; Senat, Merline; Testino, Bryanna; Dinulescu, Daniela M.; Sridhar, Srinivas (Frontiers in Oncology, 2023)
Background Ovarian cancer has long been known to be the deadliest cancer associated with the female reproductive system. More than 15% of ovarian cancer patients have a defective BRCA-mediated homologous recombination repair pathway that can be therapeutically targeted with PARP inhibitors (PARPi), such as Talazoparib (TLZ). The expansion of TLZ clinical approval beyond breast cancer has been hindered due to the highly potent systemic side effects resembling chemotherapeutics. Here we report the development of a novel TLZ-loaded PLGA implant (InCeT-TLZ) that sustainedly releases TLZ directly into the peritoneal (i.p.) cavity to treat patient-mimicking BRCA-mutated metastatic ovarian cancer (mOC). Methods InCeT-TLZ was fabricated by dissolving TLZ and PLGA in chloroform, followed by extrusion and evaporation. Drug loading and release were confirmed by HPLC. The in vivo therapeutic efficacy of InCeT-TLZ was carried out in a murine Brca2-/-p53R172H/-Pten-/- genetically engineered peritoneally mOC model. Mice with tumors were divided into four groups: PBS i.p. injection, empty implant i.p. implantation, TLZ i.p. injection, and InCeT-TLZ i.p. implantation. Body weight was recorded three times weekly as an indicator of treatment tolerance and efficacy. Mice were sacrificed when the body weight increased by 50% of the initial weight. Results Biodegradable InCeT-TLZ administered intraperitoneally releases 66 μg of TLZ over 25 days. In vivo experimentation shows doubled survival in the InCeT-TLZ treated group compared to control, and no significant signs of toxicity were visible histologically in the surrounding peritoneal organs, indicating that the sustained and local delivery of TLZ greatly maximized therapeutic efficacy and minimized severe clinical side effects. The treated animals eventually developed resistance to PARPi therapy and were sacrificed. To explore treatments to overcome resistance, in vitro studies with TLZ sensitive and resistant ascites-derived murine cell lines were carried out and demonstrated that ATR inhibitor and PI3K inhibitor could be used in combination with the InCeT-TLZ to overcome acquired PARPi resistance. Conclusion Compared to intraperitoneal PARPi injection, the InCeT-TLZ better inhibits tumor growth, delays the ascites formation, and prolongs the overall survival of treated mice, which could be a promising therapy option that benefits thousands of women diagnosed with ovarian cancer.